Розробка керуючих підсистем інтелектуального робота - Цимбал, О. М.; Мілютіна, С. С. (ХНУРЭ, 2008)
The given work is devoted to the modern developments in field of intellectual robots. The purpose of report is to represent the principles of intellectual subsystems. There is described the common structure and practical implementation of decision planning support subsystem, base on framework knowledge representation and logical model of problem solver. Other considered problem is a voice command control subsystem implementation, for technological process design and on-line robot control. All the presented subsystems are planned as parts of intellectual robot project on industrial robot RM-01 base.
Keywords: розробка керуючих підсистем; підсистема інтелектуального робота